Intelligent Transportation System With 5G Vehicle-to-Everything (V2X): Architectures, Vehicular Use Cases, Emergency Vehicles, Current Challenges, and Future Directions - Vaishali Pawar; Nilima Zade; Deepali Vora; Vaishali Khairnar; Aurenice Oliveira; Ketan Kotecha; Ambarish Kulkarni (IEEE Access)
In recent years, connected vehicle technologies emerged to provide a safer and more connected environment for transportation systems, which has further evolved into cellular vehicle-to-everything (C-V2X) technology. The current study contributes in the direction of future research of smart India @2047 in connected vehicles. The study presents the diverse aspects of 5G V2X as a comprehensive overview of Vehicle-to-Everything (V2X) technology that covers the significant scope of V2X technology, including its development, components, functionality, use cases, and future potential. It is observed that few surveys are available that cover limited aspects of 5G V2X communication technologies, with one or two preferred architectures, and only few provides the definitions of 3GPP use cases. Emergency vehicles (EMV) are identified as an important part of an emergency service, and the main goal of EMV is to reduce the response time. The study discusses the research challenges in the field of V2X and presents future directions to reduce the probability of untoward incidents and enhance the EMV response time. The work leverages by synthesizing the latest research in 5G V2X technological advancements like Multiple Input Multiple Output, Beamforming, and Integrated Sensing and Communication, highlighting the roles of 5G architectures and providing a deeper understanding of the 5GAA V2X use cases from the perspective of societal benefit. The study provides a comprehensive future research directions to the researchers on 5G V2X technologies and current research trends for smart EMV applications.